The Museum of Broken Relationships in Zagreb, Croatia, as a Museum Discourse of Spectacle of Intimacy - Herrera Feregrino, Pamela (2025)
In this society, appearance and exhibition confer existence and value as part of a process of production and objectification that dominates social life. The integration of the museum discourse, from the objects or works and their arrangement within the space that is used with its architecture, lighting and layout, to guide the visitor to navigate through the narrative of what is exhibited, is part of this process. In this context, the Museum of Broken Relationships, as a “physical and virtual public space created for the purpose of treasuring and sharing your stories of brokenness and symbolic possessions” unfolds as a paradigmatic case of this process of spectacularization of personal objects transmuted or re-signified through museum discourse. And these objects are peculiar in that they refer to the intimacy of the sentimental experience of rupture. This paperproposes the analysis of the museum discourse from the point of view of museography and curatorship in order to analyze how the proposal for the projection of intimacy as a commercial product is constructed in the physical and virtual environment of the contemporary museum.